Erythropoiesis in polycythemia vera is hyper-proliferative and has accelerated maturation - Votavová, Hana; Yoon, Donghoon; Agarwal, Archana M; Swierczek, Sabina; Prchal, Josef T (Blood cells, molecules, & diseases, 2009)
Polycythemia vera (PV) is an acquired myeloproliferative clonal disorder, characterized by augmented erythropoiesis. To better define PV pathogenesis, we performed an in vitro erythroid expansion from peripheral blood mononuclear cells of controls and PV patients and evaluated the cells for proliferation, apoptosis, erythroid differentiation, and morphology at the defined time points. PV erythroid progenitors exhibited increased proliferation at days 9-14 and accelerated maturation at days 7-14, with a larger S-phase population (40%) than controls (20%) at day 11; however, the proportion of apoptotic cells was comparable to controls. Previously, we have identified PV-specific dysregulation of several microRNAs (i.e. miR-150, 451, 222, 155, 378). We had analyzed expression profiles of selected target genes of these microRNAs based on in silico prediction and their known function pertinent to the observed PV-specific erythropoiesis differences. p27, cMYB and EPOR showed differential expression in PV erythroid progenitors at the specific stages of erythroid differentiation. In this study, we identified accelerated maturation and hyper-proliferation at early stages of PV erythropoiesis. We speculate that aberrant expression of p27, c-MYB, and EPOR may contribute to these abnormal features in PV erythropoiesis.
Keywords: Erythropoiesis; Receptors, Erythropoietin; erytroidní buňky; Cell Cycle; Cyclin-Dependent Kinase Inhibitor p27; lidé; Erythroid Cells; erytropoéza; Erythroid Precursor Cells; Polycythemia Vera; polycythaemia vera; kultivované buňky; buněčný cyklus; regulace genové exprese; Cells, Cultured; geny myb; receptory erythropoetinu; mikro RNA; inhibitor p27 cyklin-dependentní kinasy; erytroidní prekurzorové buňky; Genes, myb; MicroRNAs; Gene Expression Regulation; Humans